The Effect Of Education And Training Of Toga Processing On The Level Of Community Knowledge About The Processing Of Toga Into Traditional Medicine - Devi Ristian Octavia; Khusnul Khotimah; Dewi Indah Ayu Ardiyanti Fistalia; Emilia Rahmawati; Djati Wulan Kusumo (Jurnal MIDPRO, 2021)
Since the outbreak of Covid-19, the popularity of herbal medicines has increased. The use of TOGA is strongly influenced by public knowledge and how to use each herbal medicines for various different diseases. The use of traditional medicine must also consider the appropriate dose/dose and processing method so that the therapeutic objectives are achieved. However, not many people know how to make good traditional medicines, starting from the parts of medicinal plants that are taken to the processing stage. This study aims to see the effect of education on increasing public knowledge of the management of TOGA as a traditional medicine. The study was conducted using a one group pre-post test design. The population of this study was the community in Pajangan village who were members of a group of 36 herbal medicine entrepreneurs. The sample was taken using the consecutive sampling method. toga processing training for 3 weeks. In the fourth week, the gown processing questionnaire was again distributed to the respondents as posttest data. The effect of TOGA processing education on TOGA processing knowledge was analyzed using paired samples t-test. The results showed that education and training on TOGA processing had an impact on people's knowledge about TOGA management. The increase in knowledge measured shows that most of the respondents' knowledge has increased, from low knowledge to high knowledge. with a significance value of 0.003 which means that there is an effect of education and training in increasing public knowledge about traditional medicine processing.